PENINGKATAN PRODUKTIFITAS DAN PENCEGAHAN KEKAMBUHAN GANGGUAN JIWA DENGAN PENDEKATAN PELATIHAN EMOTIONAL FREEDOM TECHNIQUE (EFT) DAN HOME CARE DI RSUD. BANYUMAS - Suryanto, Suryanto; Harwanti, Siti; Ekowati, Wahyu (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2012)
ABSTRACT Productivity is influenced by the physical and mental health status. Mental disorders in individuals of reproductive age who are either light or heavy will impact on the decline in labor productivity (patients) who suffer. One of the psychological therapies that can reduce stress in patients with psychiatric disorders is the Emotional Freedom Technique (EFT). The purpose of research is to apply EFT training to improve the condition of our emotions, thoughts and behaviors so as to prevent the recurrence of mental illness.The study was conducted with the survey and participant observation. The data source is the patient, family, hospital health care team. Banyumas. Conducted a prospective approach with instruments such as questionnaires and observation sheets. Sampling technique using purposive sampling with the number 20. Respondents were given a training intervention EFT and home care later in the evaluation of pre-posttest. After discharge from the hospital respondents made ??observations in the home. The analysis was done descriptively. Results of the 20 respondents, primary and secondary education respectively 8 people (40%) and high school graduates there are 4 people (20%). Sex female respondents, there were 12 people (60%) and men there are 8 people (40%). pre-and posttest used before and after training EFT rise of scores by an average of 20%, on the training of how to socialize with other people increases the pre and posttest scores from an average of 35% and the increase in training on personal hygiene of the pre and posttest scores an average of 45 %. Conclusion are need socialize EFT training, home care and personnel hygiene can be a provision for mental patients before discharge and to prevent recurrence. Respondents can be more confident in life and want to work as usual. Keywords :Productivity,training, observation  Kesmasindo. Volume 5( 2) Juli  2012,  hlm. 180- 190